2008
DOI: 10.1897/07-048.1
|View full text |Cite
|
Sign up to set email alerts
|

Influences of metal‐ligand complexes on the cadmium and zinc biokinetics in the marine bacterium, Bacillus firmus

Abstract: Uptake kinetics of cadmium and zinc in gram-positive bacteria, Bacillus firmus, isolated from Hong Kong sediments were examined in the present study. The metal uptake by the bacteria was measured at different ambient free metal ion concentrations (10(-12)-10(-6) M Cd(2+) and 10(-10)-10(-6) M Zn(2+)) by adding different concentrations of total dissolved Cd and Zn and hydrophilic organic ligands (ethylenedinitrilotetraacetic acid, nitrilotriacetic acid, and citrate). Our data suggest that Cd and Zn uptake by B. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Kungolos et al 27 demonstrated that copper bioaccumulation in the photobacterium Vibrio scheri decreased with the addition of humic acid to the medium, and that free copper ions were responsible for the toxic effects. Keung et al 28 showed that Cd and Zn uptake by the bacterium Bacillus rmus correlated better with the free metal concentration than with that of hydrophilic metal complexes. Since the metals complexed in DOM are less toxic, they can be accumulated by the organisms and transferred throughout the food chain, as demonstrated in our studies.…”
Section: Discussionmentioning
confidence: 99%
“…Kungolos et al 27 demonstrated that copper bioaccumulation in the photobacterium Vibrio scheri decreased with the addition of humic acid to the medium, and that free copper ions were responsible for the toxic effects. Keung et al 28 showed that Cd and Zn uptake by the bacterium Bacillus rmus correlated better with the free metal concentration than with that of hydrophilic metal complexes. Since the metals complexed in DOM are less toxic, they can be accumulated by the organisms and transferred throughout the food chain, as demonstrated in our studies.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the ubiquity of several Bacillus species and their ability to survive under diverse conditions, the requirement of some strains of seawater for growth suggests that they could represent obligate marine bacteria with habitats in marine sediments (19, 41, 57). Additionally, even as spores, marine Bacillus such as B. licheniformis , B. foraminis and B. firmus are involved in oceanic metal biogeochemical cycles by oxidation, precipitation, bioaccumulation and manganese-oxidizing activity in hydrothermal sediments and plumes (12, 17, 24). …”
mentioning
confidence: 99%